Biomechanical performance of the Bicaval Transcatheter System for the treatment of severe tricuspid regurgitation - Crascì, Fabrizio; Cannata, Stefano; Gentile, Giovanni; Gandolfo, Caterina; Pasta, Salvatore (Frontiers in Bioengineering and Biotechnology, 2023)
Tricuspid regurgitation (TR) is a relatively common valvular disease, which can result from structural abnormalities of any anatomic part of the tricuspid valve. Severe TR is linked to congestive heart failure and hemodynamic impairment, resulting in high mortality when repaired by elective surgery. This study was undertaken to quantify the structural and hemodynamic performance of the novel Transcatheter Bicaval Valves System (TricValve) percutaneously implanted in the superior vena cava (SVC) and inferior vena cava (IVC) of two patients with severe TR and venous congestion. After developing the SVC and IVC device models, the contact pressure exerted on the vena cava wall was obtained by computational analysis. Both smoothed-particle hydrodynamics (SPH) and computational fluid dynamics were carried out to quantify caval reflux in the right atrium and the pressure field of pre- and post-TricValve scenarios, respectively. Analysis of contact pressure highlighted the main anchoring area of the SVC device occurring near the SVC device belly, while the IVC device exerted pronounced forces in the device’s proximal and distal parts. SPH-related flow velocities revealed the absence of caval reflux, and a decrease in time-averaged pressure was observed near the SVC and IVC after TricValve implantation. Findings demonstrated the potential of computational tools for enhancing our understanding of the biomechanical performance of structural tricuspid valve interventions and improving the way we design next-generation transcatheter therapies to treat the tricuspid valve with heterotopic caval valve implantation.